Recent advances in targeted nanomedicine as promising antitumor therapeutics. Issue 12 (December 2020) - Hejmady, Siddhanth; Pradhan, Rajesh; Alexander, Amit; Agrawal, Mukta; Singhvi, Gautam; Gorain, Bapi; Tiwari, Sanjay; Kesharwani, Prashant; Dubey, Sunil Kumar
Highlights: Nanocarriers with the ability to target tumors are being increasingly explored. Nanomedicine aid in maintaining a balance between efficacy and toxicity. Recent advances in nanocarriers for tumor targeting are discussed. Abstract : A tumor serves as a major avenue in drug development owing to its complexity. Conventional therapies against tumors possess limitations such as suboptimal therapeutic efficacy and extreme side effects. These display poor pharmacokinetics and lack specific targeting, with non-specific distribution resulting in systemic toxicity. Therefore, nanocarriers targeted against cancers are increasingly being explored. Nanomedicine aids in maintaining a balance between efficacy and toxicity by specifically accumulating in tumors. Nanotherapeutics possess advantages such as increased solubility of chemotherapeutics, encapsulation of multiple drugs and improved biodistribution, and can ensure tumor-directed drug delivery and release via the approaches of passive targeting and active targeting. This review aims to offer a general overview of the current advances in tumor-targeting nanocarriers for clinical and diagnostic use.